Leakage failure analysis of water wall tube in circulating fluidized bed boiler. (October 2020) - Ren, Facai; Xu, Jinsha; Si, Jun
Abstract: This paper analyzes the causes of water wall tube leakage failure in circulating fluidized bed boiler. According to the results of chemical analysis, the water wall meets the technical requirements. The difference of pearlite spheroidization degree in different regions indicates that there are different degrees of overheating in each region. The energy spectrum analysis of the surface residue in the perforation area shows that the corrosion in the perforation area is related to scale deposition.